3y=-21
y=-7
2006-10-01 13:52:16
·
answer #1
·
answered by bruinfan 7
·
1⤊
0⤋
7y + 3 = 4y - 18 (Subtract 4y and 3 from both sides)
3y = -21
y = -7
Check:
7(-7) + 3 = 4(-7) - 18
-49 + 3 = -28 - 18
-46 = -46
QED
2006-10-02 05:10:09
·
answer #2
·
answered by CSUFGrad2006 5
·
0⤊
0⤋
7y=3=4y-18
7y-4y= -18 + (-3)
3y= -21
y= -7
Plugging -7 into the original equation you have:
7(-7) +3= 4(-7) -18
-49+3= -28 + (-3)
- 46 = - 46
2006-10-01 13:58:25
·
answer #3
·
answered by WC 7
·
0⤊
0⤋
7y +3 = 4y- 18
7y= 4y- 21
3y= -21
y= -7
Prove it:
7(-7) +3 = 4(-7)-18
-49 +3 = -28-18
-49+3 = -46
-46 = -46
2006-10-01 14:04:05
·
answer #4
·
answered by soulguy85 6
·
0⤊
0⤋
7y+3=4y-18
combine same terms:
7y-4y= -18-3 (positive sign changes to negative)
3y= -21
divide both to 3
y= -7
2006-10-01 13:55:38
·
answer #5
·
answered by yeday 2
·
0⤊
0⤋
7y+3=4y-18 (Figure out Y)
-4y = -3 (Get the Y on one side)
3y = -21 (Get Y by itself by dividing both sides by 3)
3 = 3
y = -7
2006-10-01 14:05:27
·
answer #6
·
answered by the one who knows 2
·
0⤊
0⤋
First you must isolate your variables. Subtract 4y from both sides.
7y-4y+3=4y-4y-18. Now you get 3y+3=-18.
Now you need to subtract 3 from both sides to complete the isolation. 3y+3-3=-18-3. Now your problem looks like this: 3y=-21.
Now you want to divide both sides by 3 to get y by itself.
3y/3=-21/3.
y=-7.
2006-10-01 13:57:17
·
answer #7
·
answered by Melanie G 1
·
0⤊
0⤋
7y+ 3 = 4y-18
-3 -3
7y = 4y-21
-4y -4y
3y = -21
/3 /3
y= -7
2006-10-01 14:02:19
·
answer #8
·
answered by FLAKA 2
·
0⤊
0⤋
7y+3= 4y-18
-4y+3=-4y-18
------------------
3y+3=-18
-3= -3
--------------
3y= -21
3y/3= 3/-21
y= -7
2006-10-01 13:56:04
·
answer #9
·
answered by LoCA 1
·
0⤊
0⤋
y = -7
2006-10-01 13:55:02
·
answer #10
·
answered by Anonymous
·
0⤊
0⤋
7y+3=4y-18
7y-4y=-18-3
3y=-21
y=-7
2006-10-01 13:54:01
·
answer #11
·
answered by Anonymous
·
1⤊
0⤋